A caminho do Norte: cartografia dos impactos territoriais do agronegócio em Rondônia (Amazônia ocidental) - Ricardo Gilson da Costa Silva; Amanda Michalski (Confins)
We analyze the geographic route of soya, as the main product of brazilian agribusiness, and its spatial effects in the brazilian Amazon. Through of geographic cartography we problematize the territorial impacts of agribusiness in the state of Rondônia, demonstrating that the insertion of soya produced the displacement of the agricultural frontier in rondonienses subregions that had not been the object of agricultural expansion. We conclude in the Amazonia the frontier moves in protected areas, showing both the weakness of the government in territorial management and the spatial effects of agribusiness in converting forests and protected areas into agricultural space.